Perceived effects of climate change on aquaculture production in Zambia: status, vulnerability factors, and adaptation strategies - Sahya Maulu; Sahya Maulu; Oliver J. Hasimuna; Oliver J. Hasimuna; Oliver J. Hasimuna; Moses Chibesa; Ian Bbole; Joseph Mphande; Joseph Mphande; Mazuba Mwanachingwala; Mazuba Mwanachingwala; Kundananji Nawanzi; et al. (Frontiers in Sustainable Food Systems, 2024)
Aquaculture plays a critical role in Zambia's food and nutrition security. However, aquaculture is highly vulnerable to the effects of a changing climate which can lead to economic losses, and food and nutrition insecurity. In this study, we investigated the perceived effects of climate change on aquaculture production in Zambia, vulnerability factors, and adaptation strategies. We used semi-structured and structured questionnaires to collect data from aquaculture producers in all provinces across the country. Results revealed high (over 80%) awareness of climate change, primarily attributed to literacy levels and access to media. Producers perceived occurrence of climate-related changes such as rising temperature, altered rainfall patterns, cyclones frequency, and disease outbreaks, impacting production costs. Generally, the results indicate a high to medium perception of rising temperature and increased frequency of flooding and droughts across the country. Although rising temperature did not appear to affect aquaculture production cost, the frequency of droughts, floods, cyclones, and disease outbreaks showed a significant association with production costs. Identified vulnerability factors include reliance on a limited range of fish species, absence of insurance coverage, and low adoption of adaptation practices. Vulnerability levels vary across regions, with provinces in agroecological zone I (Eastern, Lusaka, Southern, and Western) showing higher vulnerability. Despite this, many producers aren't implementing adaptation measures due to financial limitations, species diversity constraints, and insufficient knowledge of alternative economic pursuits. Main adaptation strategies involve livelihood diversification and adjustments in fish cultivation periods and infrastructure. To foster aquaculture sustainability amid climate change, critical interventions such as farm insurance, research diversification in aquaculture species, and enhancing producer resilience are necessary.